Environmental, Maternal, and Socioeconomic Factors Associated with Stunting among Under-Five Children in Pengadegan Village, Sumedang Regency: A Cross-Sectional Study - Andriyani Risma Sanggul; Adhristhi Pramithaswari Firmansyah (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Stunting remains a major public health issue reflecting chronic undernutrition during early childhood. In Sumedang Regency, the prevalence of stunting is 27.6%. This study aimed to identify environmental, maternal, and socioeconomic factors associated with stunting among under-five children in Pangadegan Village, Sumedang Regency.Methods: A cross-sectional study was conducted in May 2023 among 170 children aged 5 years or younger. Data were collected through structured interviews and anthropometric measurements. Independent variables included drinking water quality, sewage facilities, maternal hemoglobin level during pregnancy, maternal nutritional status, birth weight, exclusive breastfeeding, infectious diseases, maternal education, and household income. This study performed multivariable analyses to estimate prevalence ratios (PRs) with 95% condidence intervals (CIs).Results: The prevalence of stunting was 28.8%. In adjusted analysis, sewage facilities (PR: 3.38; 95% CI: 1.25–11.28), drinking water quality (PR: 3.38%; 95% CI: 1.50–7.60), low maternal hemoglobin during pregnancy (PR: 2.64%; 95% CI: 1.05–6.64), and non-exclusive breastfeding (PR: 2.36%; 95% CI: 1.03–5.38) were significantly associated with stunting.Conclusions: Environmental sanitation and maternal factors were significantly associated with stunting. Interventions such as improving drinking water quality and sewage facilities, early detection of maternal hemoglobin during pregnancy, and implementing exclusive breastfeeding may support stunting reduction in this setting.